2019
DOI: 10.1088/1361-648x/ab531a
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of pinned magnetic moments in an antiferromagnet to a ferromagnet and its role for exchange bias

Abstract: The interaction between uncompensated pinned magnetic moments within an antiferromagnetic (AFM) layer and an adjacent ferromagnetic (FM) layer responsible for the existence of exchange bias is explored in epitaxially grown trilayers of the form FM2/AFM/FM1 on Cu3Au(0 0 1) where FM1 is ~12 atomic monolayers (ML) Ni, FM2 is 21–25 ML Ni, and AFM is 27 ML or 50 ML Ni~25Mn~75. Field cooling for parallel or antiparallel alignment of the out-of-plane magnetizations of the two FM layers does not make a difference for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Exchange bias originates from uncompensated pinned magnetic moments within the AFM, which couple to the FM layer. Since these pinned magnetic moments are distributed throughout the AFM layer, [23,[37][38][39][40][41] their coupling to the FM layer and thus the exchange-bias field depends on the intra-AFM exchange interaction. A smaller average vertical atomic spacing enhances the exchange interaction in the AFM layer.…”
Section: Resultsmentioning
confidence: 99%
“…Exchange bias originates from uncompensated pinned magnetic moments within the AFM, which couple to the FM layer. Since these pinned magnetic moments are distributed throughout the AFM layer, [23,[37][38][39][40][41] their coupling to the FM layer and thus the exchange-bias field depends on the intra-AFM exchange interaction. A smaller average vertical atomic spacing enhances the exchange interaction in the AFM layer.…”
Section: Resultsmentioning
confidence: 99%
“…As previous reported, the EB effect in some Heusler alloys can be attributed to the exchange coupling between the SG and the AFM matrix, since the short-range ordered FM clusters are assumed to be formed in the SG state during application of an external field in the cooling process. 29) Recently, it was found that H EB depends strongly on the size of the FM clusters in the AFM matrix. 30) The size of the FM clusters in the SG and SSG systems are different at varying temperatures under ZFC and FC processes, resulting in a huge difference in the EB effect.…”
mentioning
confidence: 99%